WEBBASED CSR COMMUNICATION REQUIREMENT FOR MANAGEMENT BASED ON MEDIA RICHNESS THEORY - Ati Harmoni (Jurnal Ilmiah Ekonomi Bisnis, 2012)
The purpose of this study was to identify the CSR communication requirement by the management through the framework of Media Richness. The study was conducted by doing case studies on three mining companies operating in Indonesia. CSR communication requirement by management in terms of timeliness, presentation and organization, accessibility, and interaction, while the feature of the websites that is capable to facilitate the needs of management for CSR communication were immediacy, multiple cues, language variety, multiple addressability, personal sources, computer processable memory, externally recordable, and concurrency. The study showed that the communication requirements of management that are considered critical resulting in the use of the web features moderate to high, while the communication requirements that are considered non-critical by management resulting in low to moderate usage of web features. CSR communication need that was considered critical by all three companies was accessibility. This resulted in the high use of multiple addressability feature on the web.   Key words: CSR communication, website, stakeholders, media richness framework